O licenciamento como instrumento de regulaç\~ao ambiental: Desafios, propostas e perspectivas - Luiz Felipe Monteiro Seixas; Nilo Luiz Saccaro Júnior (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
– This work proposes to examine the current scenario of environmental licensing procedures in Brazil, from a theoretical approach (legal, economic and regulatory) concerning the theme. Keeping in mind that the discussions regarding the environmental licensing procedure continue to guide the debate in the public and private spheres (including the elaboration of a bill in progress before the Federal Legislative Power), the text has as scope, at first, to describe the main regulatory frameworks related to licensing, as well as the bottlenecks and problems identified by specialized literature; soon after, some discussions and proposals for improvement of the environmental regulation instrument will be presented, with the purpose of subsidizing the debate from a technical and propositional view on the matter. Among the main arguments and conclusions exposed throughout the text, there is the need to recognize the licensing as an instrument of environmental regulation, able to reduce/ correct negative externalities arising from activities and undertakings potentially polluting, but, for this very reason, holding instrumental character, which requires appropriate improvement and optimization from the regulatory point of view.
10419/284864
Keywords: K20; K32; 330; environmental licensing; environmental regulation; environmental agencies; regulatory competence